Case report: Prazosin augmentation for treating comorbid treatment-resistant depression and chronic post-traumatic stress disorder - Guo, Ping; Fang, Yu; Feng, Ming; Zhao, Xudong; Wang, Shikai; Qian, Mincai; Huang, Juanjuan; Chen, Huanxin (Frontiers in Psychiatry, 2022)
Psychological trauma in childhood can lead to protracted depression and poor response to conventional antidepressants. Previous studies have shown that prazosin can help eliminate suicidal ideation and improve sleep quality in patients with post-traumatic stress disorder (PTSD). In this case report, we describe that prazosin treatment was feasible and well tolerated by a patient with treatment-resistant depression (TRD) caused by chronic PTSD. Prazosin had rapid and remarkable antidepressant effects with few adverse effects. Moreover, the patient showed significant improvements in neurocognitive measurements. Our preliminary results suggest that further clinical trials are needed to determine the efficacy and safety of prazosin in TRD patients comorbid with PTSD or in TRD patients caused by psychological trauma.